-3c+10c+2+-5=

Simple and best practice solution for -3c+10c+2+-5= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3c+10c+2+-5= equation:


Simplifying
-3c + 10c + 2 + -5 = 0

Reorder the terms:
2 + -5 + -3c + 10c = 0

Combine like terms: 2 + -5 = -3
-3 + -3c + 10c = 0

Combine like terms: -3c + 10c = 7c
-3 + 7c = 0

Solving
-3 + 7c = 0

Solving for variable 'c'.

Move all terms containing c to the left, all other terms to the right.

Add '3' to each side of the equation.
-3 + 3 + 7c = 0 + 3

Combine like terms: -3 + 3 = 0
0 + 7c = 0 + 3
7c = 0 + 3

Combine like terms: 0 + 3 = 3
7c = 3

Divide each side by '7'.
c = 0.4285714286

Simplifying
c = 0.4285714286

See similar equations:

| 0=x*2.5 | | 4x^2-14+2=0 | | 40+55h=190 | | 2k^4+12k^2+9=0 | | 0.3+y=2 | | 4x^2+44x-122=0 | | 6j+6=9j | | -5a+28a= | | 0=x/2.5 | | 9p-13p+12p+19q= | | 2(4.5+m)+3=4(m-3)+5.5 | | 2(4.5+m)+3=4(m-3)5.5 | | 2x+-1-6=10+-10x+6 | | 12d+5e-7d= | | 1=4.5-2p+2.333333p | | 5k(k-2)-8k=-34 | | 1+x-6x=11 | | 5x=2x+42 | | 4p+8p-p= | | -7y=9-10y | | -5t-4=2t+14 | | 5x+1y=112 | | 1.25x=15.25 | | 6w+12=48 | | (5x-2)(3x+4)=(3x-5)(5x+1)+15 | | 4x+152=6x+166 | | 4k^2+3k-7=0 | | 9p+5q-2p= | | X-3+8=20 | | 3p+9=6p | | 5x-4+3=19 | | 5b-12b-90= |

Equations solver categories